Fetal hydrometrocolpos with pre‐axial mirror polydactyly as a new variant of McKusick‐Kaufman syndrome. Issue 1 (14th June 2020) - Traisrisilp, Kuntharee; Nunthapiwat, Sujinun; Luewan, Suchaya; Tongsong, Theera
Abstract: This report describes a variant of McKusick‐Kaufman syndrome presenting with a large fetal abdominal cyst of hydrometrocolpos at 37 weeks of gestation. The diagnosis was based on the ultrasound findings of a large homogeneous hypoechoic cyst (diameter of >10 cm) with incomplete septum, thickened wall, superiorly connecting to the dilated uterus, consistent with hydrometrocolpos. Additionally, pre‐axial mirror polydactyly of the left foot was suspected. Postnatal examination/work‐up confirmed the prenatal findings. This is the first report of prenatal diagnosis of hydrometrocolpos with complex polydactyly of mirror image pre‐axial duplications containing nine toes instead of six‐toe postaxial polydactyly.